SIFAT FISIK DAN ORGANOLEPTIK MI BASAH DARI PATI SAGU DENGAN PENAMBAHAN EKSTRAK DAUN KELOR (Moringa oleifera) - Nida El Husna (Jurnal Teknologi & Industri Hasil Pertanian, 2017)
Sago starch as local food rich in carbohydrates and crude extract of moringa leaves that rich in protein have potential to be developed as a raw material for wet noodle. The objective of this research was to determine the effect of percentage of moringa leaf extract (5%, 10%, 15%) and the filtering process of extracts (with and without screening) on the physical and sensory properties of wet noodle. This study was conducted using completely randomized design consisted of two factors with three replications. Analysis of wet noodles includes of cooking time, cooking loss, water absorption, percentage of breaking noodles, sensory (hedonic) test of color, aroma, taste, and texture. The results showed that the higher of percentage of moringa leaves extract increased the cooking time, cooking loss, and percentage of breaking noodles. Moringa leaf extract with the screening process decreased the cooking time and breaking percentage of noodles. The best treatment was obtained from the addition of moringa leaves extract of 5 % and with the filtering process of extracts.